Economic burden of breast cancer in northern Serbia - Milovic, Marko; Tamas, Tatjana; Crnobrnja, Veljko; Paut Kusturica, Milica (Frontiers in Public Health, 2023)
Introduction Breast cancer is the most common cancer in terms of incidence and mortality among all cancers in women in Vojvodina, the northern region of Serbia. In addition to the effectiveness and safety of therapy, it is important to put emphasis on the cost of treatment, as well as on the optimal allocation of limited resources. Objectives This study aimed to assess the overall economic burden of breast cancer in Vojvodina, as well as the ratio of direct and indirect costs in 2019. Materials and methods Costs were estimated using Cost of Illness (COI) evaluation, from a social perspective, based on the prevalence of the disease. The total costs included both direct and indirect expenditures. Direct costs associated with breast cancer comprised expenses linked to screening, hospital treatment, outpatient care, and prescribed medications. Indirect costs were estimated using a human capital approach, encompassing expenditures tied to lost productivity arising from sick leave, early retirement, and premature death. Results The total cost of breast cancer in Vojvodina during 2019 was estimated to be 15 million euros. Among the total cost, direct costs accounted for 5 million euros, representing 34% of the overall expenses. Hospital treatment costs accounted for 76% of the direct costs, while screening costs represented 1%. Indirect costs amounted to 10 million euros, constituting 66% of the total cost. The primary driver was attributed to production losses caused by premature retirement, which accounted for 50% of the indirect costs. Conclusion Breast cancer is a huge financial burden on both the health system and society in Vojvodina, accounting for 0.12% GDP. The dominance of indirect costs in total costs, can provide significant guidance to decision-makers in the healthcare system in terms of better allocation of limited resources to breast cancer prevention and early detection strategies.